1970
DOI: 10.5755/j01.eee.108.2.155
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid GA-PSO Approach Based on Similarity for Various Types of Economic Dispatch Problems

Abstract: Economic dispatch problem is an optimization problem where objective function is highly nonlinear. In this paper, an efficient method based on hybrid genetic algorithm- particle swarm optimization (GA-PSO) for economic dispatch (ED) problem is proposed. In the proposed method, children created by using similarity measurement between mother and father chromosomes relationship. The feasibility of the proposed approach is demonstrated for solve various types of economic dispatch (ED) problems in power systems suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…An efficient method based on a hybrid genetic algorithm-particle swarm optimization (GA-PSO) is presented for various types of economic dispatch (ED) problem [40]. The arithmetic crossover operator is used as crossover operator in the genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…An efficient method based on a hybrid genetic algorithm-particle swarm optimization (GA-PSO) is presented for various types of economic dispatch (ED) problem [40]. The arithmetic crossover operator is used as crossover operator in the genetic algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…The obtained results for the 6-unit system using the hybrid PSO-GSA method are given in Table 3 and the results are compared with other methods reported in literature, including GA, PSO and IDP [21], RGA and GA-PSO [22]. It can be observed that PSO-GSA can get total generation cost of 15,441 ($/hr) and power losses of 12.2417 (MW), which is the best solution among all the methods.…”
Section: Test Case 1: 6-unit Systemmentioning
confidence: 99%
“…It has been applied on many real-time problems. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Its mechanism of solution improvement and information sharing procedure are unique and di®er from that used in the ABC algorithm. It consists of using special parameter called Velocity (v), which is used to control the degree of improvement to be conduct on the solution based on its previous state.…”
Section: Introductionmentioning
confidence: 99%